Clinical, histopathological and prognostic features of primary cutaneous acral CD8+ T‐cell lymphoma and other dermal CD8+ cutaneous lymphoproliferations: results of an EORTC Cutaneous Lymphoma Group workshop. (1st May 2022) - Kempf, Werner; Petrella, Tony; Willemze, Rein; Jansen, Patty; Berti, Emilio; Santucci, Marco; Geissinger, Eva; Cerroni, Lorenzo; Maubec, Eve; Battistella, Maxime; Goodlad, John; Guenova, Emmanuella; et al.
Abstract: Background: The differential diagnosis of atypical dermal nonepidermotropic CD8 + lymphocytic infiltrates includes a heterogeneous spectrum of lymphoproliferations with overlapping histological and phenotypic features, but divergent clinical manifestations and prognoses. As these neoplasms are rare, more data on their clinicopathological presentation and course are needed. Objectives: To assess the clinical, histological and immunophenotypic features; outcomes of; and differences between dermal CD8 + lymphoproliferations. Methods: Retrospective analysis of a series of 46 patients and biopsies by the international EORTC Cutaneous Lymphoma Group. Results: The dermal CD8 + lymphoproliferations (n = 46) could be assigned to one of three groups: (i) cutaneous acral CD8 + T‐cell lymphoma (n = 31), characterized mostly by a solitary nodule arising at acral sites, a monotonous dermal infiltrate of small‐to‐medium‐sized CD8 + lymphocytes with a characteristic dot‐like pattern of CD68, a low proliferation rate and an excellent prognosis; (ii) primary cutaneous CD8 + peripheral T‐cell lymphoma, unspecified/NOS (n = 11), presenting with one or multiple rapidly evolving tumours, mostly medium‐sized pleomorphic CD8 + tumour cells with expression of several cytotoxic markers, and high proliferative activity; and (iii) cutaneous CD8 + lymphoproliferations (n = 4), associated with congenital immunodeficiency syndromes in two patients with persisting localized or disseminated violaceous to brownish plaques on the extremities, a histiocyte‐rich infiltrate of mostly small CD8 + lymphocytes with subtle atypia and a protracted course; and papular CD8 + eruptions in two patients with acquired immunosuppression. Conclusions: A constellation of distinct clinical, histopathological and phenotypic features allows discrimination and assignment of dermal CD8 + infiltrates into distinct disease entities. Primary cutaneous acral CD8 + lymphoma, assigned a provisional category in current lymphoma classifications, is a distinct and reproducible entity. A correct diagnosis is essential to avoid unnecessarily aggressive treatment for indolent CD8 + lymphoproliferations and to identify cases with underlying immuno‐deficiency or potential for dismal outcome.